Role of Ubiquilins for Brown Adipocyte Proteostasis and Thermogenesis - Muley, Carolin; Kotschi, Stefan; Bartelt, Alexander (Frontiers in Endocrinology, 2021)
The acclimatization of brown adipose tissue (BAT) to sustained cold exposure requires an adaptive increase in proteasomal protein quality control. Ubiquilins represent a recently identified family of shuttle proteins with versatile functions in protein degradation, such as facilitating substrate targeting and proteasomal degradation. However, whether ubiquilins participate in brown adipocyte function has not been investigated so far. Here, we determine the role of ubiquilins for proteostasis and non-shivering thermogenesis in brown adipocytes. We found that Ubqln 1, 2 and 4 are highly expressed in BAT and their expression was induced by cold and proteasomal inhibition. Surprisingly, silencing of ubiquilin gene expression (one or multiple in combination) did not lead to aggravated endoplasmic reticulum (ER) stress or inflammation. Moreover, ubiquitin level and proteasomal activity under basal conditions were not impacted by loss of ubiquilins. Also, non-shivering thermogenesis measured by norepinephrine-induced respiration remained intact after loss of ubiquilins. In conclusion, ubiquilin proteins are highly abundant in BAT and regulated by cold, but they are dispensable for brown adipocyte proteostasis and thermogenesis.